Presumptive Iatrogenic Microcystin‐Associated Liver Failure and Encephalopathy in a Holsteiner Gelding. (9th September 2016) - Mittelman, N.S.; Engiles, J.B.; Murphy, L.; Vudathala, D.; Johnson, A.L.
Abstract : An 8‐year‐old Holsteiner gelding was presented for evaluation of anorexia, obtundation, icterus, and mild colic signs of 48 hours duration. History, physical examination, and initial diagnostics were suggestive of hepatic disease and encephalopathy. Microcystin toxicosis was suspected based on historical administration of a cyanobacteria supplement, associated serum biochemistry abnormalities, and characteristic histopathological changes. Microcystin contamination was confirmed in both supplement containers fed to the horse. Fulminant hepatic failure and encephalopathy progressed resulting in euthanasia. Necropsy findings were consistent with microcystin induced liver failure.